Correlation of Rationality Empiric Antibiotic with Clinical Outcome in Hospital Acquired Pneumonia Patients - Brilyani, Anisa Ellen; Andayani, Tri Murti; Endarti , Dwi (Journal of Health Economic and Policy Research (JHEPR), 2025)
Background: Irrational use of antibiotics causes high mortality rates from Hospital Acquired Pneumonia (HAP), resulting in the worsening of patients’ clinical outcomes. This study aims to determine the correlation between the rationality of empirical antibiotic use and the clinical outcomes of HAP patients. Methods: The research was conducted using a retrospective cohort and consecutive sampling with a research sample of adult patients diagnosed with HAP at Gadjah Mada University Academic Hospital who were treated in the period January 2021- October 2023. HAP patients who received empiric antibiotics for less than 48 hours, had infections other than HAP, and cancer were excluded from this study. The rationality of antibiotics was assessed using a Gyssens’ flow diagram, the patients’ clinical outcomes were seen on days 2 to 3rd of empirical antibiotic use, and the chi-square test to see the correlation of antibiotic rationality with clinical outcomes. Results: A total of 52.63% of patients received rational empirical antibiotics, and 47.37% received irrational empirical antibiotics. Clinical outcomes that did not improve often occurred in the rational group, specifically in 13 patients out of 40 patients. The results of the chi-square test showed that the rationality of empirical antibiotic use did not correlate with clinical outcomes in HAP patients at Gadjah Mada University Academic Hospital, with a p-value of 0.317. Conclusion: The rationality of empirical antibiotic use does not have a significant relationship with clinical outcomes. Keywords: Clinical Outcome, Empiric Antibiotics, Gyssens, Hospital-Acquired Pneumonia (HAP), Rationality.